Controller design for permanent magnet synchronous generator - wind turbine - Saw, Stephen. (2012)
The generation of electrical power from wind farms is developing rapidly with the worldwide installed capacity. Being a promising alternative energy source nowadays, the technology for wind energy systems have gained popular. And because of the increasing wind power penetration, the improvements of the control strategies become a new challenge in order to extract maximum power from the wind. The implemented technology for extracting maximum power from the wind is needed to supply enough to the grid. This paper focuses on the control of the generator side converter which led fully control of the rotor speed of the generator. Field orientation control (FOC) control strategy is used to achieve Maximum Power Point Tracking (MPPT). These model are implemented and performed with the aid of MATLAB/Simulink to observe the simulation results.